2022
DOI: 10.3233/wor-210692
|View full text |Cite
|
Sign up to set email alerts
|

The role of at home workstation ergonomics and gender on musculoskeletal pain

Abstract: BACKGROUND: The recent mandate for university faculty and staff to work-from-home (WFH) during the COVID-19 pandemic has forced employees to work with sub-optimal ergonomic workstations that may change their musculoskeletal discomfort and pain. As women report more work-related musculoskeletal discomfort (WMSD), this effect may be exacerbated in women. OBJECTIVE: The purpose of this study was to describe university employee at-home office workstations, and explore if at-home workstation design mediates the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 39 publications
0
21
1
1
Order By: Relevance
“…Another study showed that the mere migration to telework at the beginning of the COVID-19 pandemic exerted no effect on the intensity of neck pain among the participants but that the greater intensity of this pain was related to worse ergonomic conditions of the home workstation, the number of hours working in the computer, and fewer breaks during the workday 10 . In the same sense, other studies pointed out that the musculoskeletal complaints among teleworkers were mediated by inadequate ergonomic conditions and were related to the intensity of telework (days per week of telework) only when the telework conditions were deficient, such as lack of a home workplace where the employees could concentrate for work 22,24–26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that the mere migration to telework at the beginning of the COVID-19 pandemic exerted no effect on the intensity of neck pain among the participants but that the greater intensity of this pain was related to worse ergonomic conditions of the home workstation, the number of hours working in the computer, and fewer breaks during the workday 10 . In the same sense, other studies pointed out that the musculoskeletal complaints among teleworkers were mediated by inadequate ergonomic conditions and were related to the intensity of telework (days per week of telework) only when the telework conditions were deficient, such as lack of a home workplace where the employees could concentrate for work 22,24–26 …”
Section: Discussionmentioning
confidence: 99%
“… 10 In the same sense, other studies pointed out that the musculoskeletal complaints among teleworkers were mediated by inadequate ergonomic conditions and were related to the intensity of telework (days per week of telework) only when the telework conditions were deficient, such as lack of a home workplace where the employees could concentrate for work. 22 , 24 26 …”
Section: Discussionmentioning
confidence: 99%
“…For those employees with MSP, pain was increased when they did not have access to a dedicated workstation. Employees who have MSP are likely to need a tailored workspace, with appropriate equipment to assist with managing their condition [ 38 ], and may require support from their employers to optimise their workspace away from the traditional office. Support may include equipment but also modifications to job design to enable flexibility, so employees can tailor their work to their capacity, which is particularly important in conditions where symptoms are variable.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini selaras dengan studi yang dilakukan di Jepang dalam skala besar, menyimpulkan bahwa peningkatan kerja dari rumah berhubungan dengan LBP pada pekerja kantoran selama pandemic Covid-19 (Minoura et al, 2021). Tidak hanya LBP, gangguan musculoskeletal lain yang dirasakan adalah nyeri leher (Moretti et al, 2020), rasa tidak nyaman pada mata (Gerding et al, 2021) serta nyeri pada bahu (MacLean et al, 2022). Prevalensi nyeri leher/bahu, nyeri pada siku dan pergelangan tangan, ketegangan mata meningkat saat lockdown.…”
Section: Pembahasanunclassified